Tests of Lorentz Symmetry in Single Beta Decay - Jorge S. Díaz (Advances in High Energy Physics)
Low-energy experiments studying single beta decay can serve as sensitive probes of Lorentz invariance that can complement interferometric searches for deviations from this spacetime symmetry. Experimental signatures of a dimension-three operator for Lorentz violation which are unobservable in neutrino oscillations are described for the decay of polarized and unpolarized neutrons as well as for measurements of the spectral endpoint in beta decay.